2011
DOI: 10.1002/lt.22393
|View full text |Cite
|
Sign up to set email alerts
|

Place of liver transplantation in the treatment of hepatocellular carcinoma in the normal liver

Abstract: Hepatocellular carcinoma (HCC) is a relatively common cancer and occurs mainly in patients with liver cirrhosis (85%-95%). A significant number of cases are, however, diagnosed in normal and noncirrhotic/nonfibrotic livers. In contrast to HCC in a cirrhotic liver, noncirrhotic hepatocellular carcinoma (NC-HCC) predominantly occurs in young and healthy female patients in their 30s, and the diagnosis is frequently made at an advanced stage in the absence of a clear etiological factor. [1][2][3] The same holds tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 45 publications
0
4
0
1
Order By: Relevance
“…The other known risk factors for NC-HCC recurrence after partial liver resection are incomplete tumor resection, multiple tumors, poor tumor differentiation, absence of tumor capsule and perioperative administration of blood transfusion [10,32,35,[37][38][39]. Liver transplantation will be futile in those patients with aggressive tumor biology whereas transplantation may be justified in patients with milder tumor behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The other known risk factors for NC-HCC recurrence after partial liver resection are incomplete tumor resection, multiple tumors, poor tumor differentiation, absence of tumor capsule and perioperative administration of blood transfusion [10,32,35,[37][38][39]. Liver transplantation will be futile in those patients with aggressive tumor biology whereas transplantation may be justified in patients with milder tumor behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of published studies on HCC in the absence of cirrhosis included patients undergoing either resection or liver transplantation. 5, 810 Furthermore, most studies reported data from tertiary referral centers 1112 and may not be representative of the actual prevalence and risk factors of HCC in the absence of cirrhosis in the general population. Given that most strategies for preventing HCC, including surveillance and chemoprevention, have targeted individuals with cirrhosis, it is important to obtain a better understanding about the development of HCC in the absence of cirrhosis because of its potential implications on current clinical paradigms.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the dogma that partial liver resection is "the" therapeutic gold standard in these patients, 5-year recurrence rates are very high ranging from 40 % to 70 %. LT might therefore be of value both in the treatment of initially non-resectable HCC or in case of recurrence after resection (Lerut et al 2011). The ELTR-ELITA analysis, dealing with 62 patients with initially "non-resectable" NC-HCC, confirmed that excellent 5-year disease-free survival rates of 60 % and 48 % can be obtained after primary and salvage LT for intrahepatic recurrence (Mergental et al 2012).…”
Section: Hepatobiliary Oncologymentioning
confidence: 87%